Handbook of Experimental Phenomenology : Visual Perception of Shape, Space and Appearance - Albertazzi, Liliana (Chichester, West Sussex, UK : John Wiley & Sons., 2013)
While the scientific study of vision is well-advanced, a universal theory of qualitative visual appearances (texture, shape, colour and so on) is still lacking. This interdisciplinary handbook presents the work of leading researchers around the world who have taken up the challenge of defining and formalizing the field of'experimental phenomenology'. Presents and discusses a new perspective in vision science, and formalizes a field of study that will become increasingly significant to researchers in visual science and beyondThe contributors are outstanding sc.
pt. I. Linking psychophysics and qualities -- pt. II. Qualities in space, time, and motion -- pt. III. Appearances -- pt. IV. Measurement and qualities.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Visual perception; Psychophysics; Phenomenological psychology; PSYCHOLOGY -- Physiological Psychology; Phenomenological psychology; Psychophysics; Visual perception; Electronic books